Analysis of Historical Munasabah Between Shahih Bukhari No. 1360 and Al-Qur’an Surah At-Taubah Ayat 113 - Hati Nasution, Pelita; Usman, Usman; Husein, Nixson (International Journal of Educational Research & Social Sciences, 2025)
This study examines the historical Munasabah between Ṣaḥīḥ al-Bukhārī Hadith No. 1360 and the Qur‘anic verse Surah At-Tawbah verse 113. The main issue addressed in this research is the alleged chronological inconsistency between the hadith event that occurred in Mecca before the Hijrah and the revelation of AtTawbah verse 113, which is classified as a Madinan verse. This study aims to explain the meaning of Ṣaḥīḥ al-Bukhārī Hadith No. 1360 and analyze the historical coherence between the hadith and the Qur‘anic verse using a historical Munasabah approach. This research employs a qualitative method with a library research design. Primary data sources include the Qur‘an and Ṣaḥīḥ al-Bukhārī, while secondary sources consist of tafsir books, hadith studies, and other relevant literature. The methods applied are sanad and matn criticism, analysis of asbāb alwurūd and asbāb al-nuzūl, and historical-chronological analysis. The findings reveal that Ṣaḥīḥ al-Bukhārī Hadith No. 1360 has an authentic chain of transmission and a valid text. The apparent chronological discrepancy does not indicate a real contradiction but reflects thematic relevance rather than strict temporal linearity. Thus, the relationship between the hadith and the Qur‘anic verse remains harmonious and complementary.